Enhancing the quality of kinesthetic motor imagery for complex motor skills through simulated muscle activation color visualization: Evidence from time-frequency and functional connectivity analyses - Xiaogang Ma; Bing Shi (NeuroImage)
It is well established that providing visual guidance within demonstration models positively influences the quality of kinesthetic motor imagery (kMI) for complex motor skills. Given that action execution and kMI share several underlying mechanisms, we hypothesize that color-coded visual cues indicating muscle activation in demonstration models can enhance the quality of kMI in the acquisition of complex motor skills. To test this hypothesis. We employed AnyBody Modeling System to develop demonstration model videos of complex motor skills. Thirty participants (mean age = 20.3 ± 0.6 years; 7 men and 8 women per group) were assigned to an experimental group, which engaged in kMI after viewing demonstration videos supplemented with simulated muscle activation color cues, or to a control group, which performed kMI following videos without such cues. All participants scored above 5 on the Motor Imagery Questionnaire-2 (MIQ-2). The vividness of kMI was assessed using the Vividness of Motor Imagery Questionnaire-2 (VMIQ-2). A 64-channel EEG cap was utilized for data acquisition. Changes in alpha and beta range oscillations during kMI were examined, and region of interest (ROI) analysis was conducted to extract the correlation coefficient matrix among kMI-related subcortical nuclei. Our results demonstrated that the vividness of kMI in the experimental group was significantly higher than that in the control group by 19.9 % (P < 0.05). Conversely, alpha event-related synchronization (ERS) in the parietal and occipital regions, as well as ERS in the frontal, central, and temporal regions, were significantly lower in the experimental group compared to the control group. The source-functional connectivity results revealed that the primary differences between the experimental and control groups were concentrated between the left V1 and right V1, as well as among the posterior parietal cortex (PPC), dorsolateral prefrontal cortex (DLPFC), and primary motor cortex (M1). In conclusion, the demonstration model, which incorporates simulated muscle activation and color visualization, enhances the vividness of kMI in complex motor skills. This enhancement is associated with the selective inhibition of the frontal, central, and temporal brain regions, the activation of the occipital and parietal regions within brain rhythmic activity, and increased information flow between the occipital-parietal and frontal-parietal brain regions.